Total Hip Revision with a Custom Acetabular Component and Femoral Allograft-Prosthetic Composite as Salvage for Failed Unstable Megaprosthesis in an Adolescent Patient: A Case Report at 19-Year Follow-up Duration. Issue 4 (4th October 2021) - Phocas, Alexandra; Holst, David C.; Angerame, Marc R.; Kurkis, Gregory; Dennis, Douglas A.
Abstract : Case: A 13-year-old girl presented after a right proximal femur replacement after proximal femoral resection for treatment of an Ewing sarcoma. She presented after multiple episodes of recurrent instability with her hip endoprosthesis chronically dislocated. Her hip was revised to a custom, constrained metal-on-metal acetabular component with a small iliac flange. The femoral component was revised to an allograft-prosthetic composite. She has been free of malignancy recurrence, implant failure, or dislocation at 19-year follow-up duration. Conclusion: Dislocation of the prosthetic hip can be a challenging postoperative complication, particularly when associated with a tumor megaprosthesis in a pediatric age group. This is further compounded in the presence of deficient pelvic bone stock. Restoration of bone stock is optimal, but when impossible, custom components may be necessary to establish hip stability.